2022
DOI: 10.3389/fonc.2022.942678
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of anlotinib plus programmed death-1 blockade versus anlotinib monotherapy as second or further-line treatment in advanced esophageal squamous cell carcinoma: A retrospective study

Abstract: BackgroundBoth anlotinib and programmed death-1 (PD-1) blockade have been approved for the second-line treatment of metastatic esophageal squamous cell carcinoma (ESCC). However, the combination of these two therapies has not been evaluated. This study investigated the efficacy and safety of anlotinib, a novel multitarget tyrosine kinase inhibitor targeting tumor angiogenesis, combined with PD-1 blockade as second or further-line treatment for advanced ESCC.MethodsBetween January 2019 and February 2021, 98 adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Combination anti-PD-1 and targeted therapy is increasingly widely used for treatment of several malignancies such as gastric cancer, non-small cell lung cancer, and liver cancer, but its use is uncommon in ESCC[ 18 - 20 ]. Liu et al [ 5 ] retrospectively reviewed and analyzed 98 patients with advanced ESCC, wherein 48 patients were administered anlotinib plus an anti-PD-1 and remaining 50 patients received anlotinib monotherapy. Overall, patients receiving the combination therapy showed a longer PFS (5.4 vs. 3.0 mo) with a higher ORR (23.9% vs. 10.4%) than the patients receiving anlotinib monotherapy[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination anti-PD-1 and targeted therapy is increasingly widely used for treatment of several malignancies such as gastric cancer, non-small cell lung cancer, and liver cancer, but its use is uncommon in ESCC[ 18 - 20 ]. Liu et al [ 5 ] retrospectively reviewed and analyzed 98 patients with advanced ESCC, wherein 48 patients were administered anlotinib plus an anti-PD-1 and remaining 50 patients received anlotinib monotherapy. Overall, patients receiving the combination therapy showed a longer PFS (5.4 vs. 3.0 mo) with a higher ORR (23.9% vs. 10.4%) than the patients receiving anlotinib monotherapy[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 5 ] retrospectively reviewed and analyzed 98 patients with advanced ESCC, wherein 48 patients were administered anlotinib plus an anti-PD-1 and remaining 50 patients received anlotinib monotherapy. Overall, patients receiving the combination therapy showed a longer PFS (5.4 vs. 3.0 mo) with a higher ORR (23.9% vs. 10.4%) than the patients receiving anlotinib monotherapy[ 5 ]. Additionally, Tang et al [ 6 ] reported that a postoperative recurrent ESCC patient receiving a combination therapy of nivolumab and anlotinib showed CR.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike sunitinib, zoledronic acid combined with radiation has a radiosensitizing effect on ESCC cells by blocking the cell cycle between S and G2/M phases, leading to increased cell death [ 118 ]. Anlotinib selectively inhibits VEGFR and contributes to the inhibition of tumor growth and metastasis, significantly improving PFS and disease control rate (DCR) in patients with advanced ESCC, and is now entering second-line and further-line treatment in ESCC [ 119 ]. Cisplatin-based CCRT toxicity is difficult to tolerate in patients with unresectable advanced ESCC, and RT combined with cisplatin and anlotinib or RT combined with paclitaxel and erlotinib can achieve better anti-esophageal cancer outcomes [ 110 , 120 ].…”
Section: Reversal Strategy Of Escc Radioresistancementioning
confidence: 99%